The effect of transformational leadership on organizational performance through the mediating role of organizational culture in higher education institutions in Iraq - Waham, Mohammed Ahmed (2022)
The aim of this research was to determine the effect of transformational leadership on organizational performance through the mediating role of organizational culture in higher education institutions (HEIs) in Iraq. Transformative leadership was the main theory used in this study. This theory stated that the role of a transformative leader in influence his or her subordinates through motivation, intellectual stimulation, caring, and charismatic role model. Based on the research questions, four main hypotheses were developed and statistically tested, the population (N = 6,294) in this study comprised the academic staff. A sample was selected by using stratified random sampling. A sample size (n = 387) was determined by using Krejcie and Morgan's table of sample sizes. Data were collected using a questionnaire as an instrument. This research used Structural Equation Modelling (SEM) to test the hypotheses. The findings showed a strong effect between transformational leadership and organizational culture = (=0.590, p<0.05), followed by an effect between the performance of the organizations and its culture = (=0.540, p<0.05) and followed by an effect between transformational leadership and organizational performance = (=0.500, p<0.05). The main finding of this study revealed a significant influence of transformational leadership on organizational performance partially mediated by organizational culture. In conclusion, the findings showed that individual consideration is pertinent for transformative leaders in higher education in Iraq. The key implication of the study is that the model of transformative leadership developed could be used to enhance higher education performance provided that the organizational culture among the staff is nurtured.